2017
DOI: 10.1016/j.celrep.2017.06.082
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Enzymes Coalesce in G Bodies under Hypoxic Stress

Abstract: SUMMARY Glycolysis is upregulated under conditions such as hypoxia and high energy demand to promote cell proliferation, although the mechanism remains poorly understood. We find that hypoxia in Saccharomyces cerevisiae induces concentration of glycolytic enzymes, including the Pfk2p subunit of the rate-limiting phosphofructokinase, into a single, non-membrane-bound granule termed the “glycolytic body” or “G body”. A yeast kinome screen identifies the yeast ortholog of AMP-activated protein kinase, Snf1p, as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(228 citation statements)
references
References 49 publications
7
203
0
1
Order By: Relevance
“…This revealed preferential interaction of Eno1 with the 3′ regions of cytoplasmic tRNAs, which are suitable RNAs to interact with to achieve an anti‐phase separation effect. Notably, several other glycolytic enzymes were reported to form phase‐separated, cytoplasmic “G bodies” following hypoxic stress (Miura et al , ; Jin et al , ). It seems possible that formation of these bodies might be regulated by protein–RNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed preferential interaction of Eno1 with the 3′ regions of cytoplasmic tRNAs, which are suitable RNAs to interact with to achieve an anti‐phase separation effect. Notably, several other glycolytic enzymes were reported to form phase‐separated, cytoplasmic “G bodies” following hypoxic stress (Miura et al , ; Jin et al , ). It seems possible that formation of these bodies might be regulated by protein–RNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…RNA also regulates the nucleation and spatiotemporal distribution of membraneless organelles [62,63]. Even G-bodies, which are composed of proteins involved in glucose metabolism, require RNA for biogenesis [64]. RNA can also affect the material properties of protein droplets [48,60].…”
Section: Molecular Determinants Of Protein Phase Separation In Vitro mentioning
confidence: 99%
“…Second, although protein aggregates in disease are considered harmful, accumulating evidence suggests that they could be an initial rescue mechanism of the cell to sequester the more toxic protein oligomers [149,150]. Third, numerous assemblies function as storage granules, as they sequester proteins and other biomolecules under times of stress or quiescence for later reuse [64,151]. Fourth, by concentrating receptors and signaling molecules, a cell can amplify certain signaling pathways.…”
Section: Figurementioning
confidence: 99%
“…In yeast, the presence of G bodies correlates with accelerated glucose consumption, and impairing G body formation leads to the accumulation of upstream glycolytic metabolites (Jin et al, 2017). These data suggest that during hypoxic stress, when oxidative phosphorylation is inhibited, G bodies form to enhance the rate of glycolysis by concentrating glycolysis enzymes.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, we and others demonstrated that glycolysis enzymes coalesce into membraneless cytoplasmic granules called glycolytic bodies (G bodies) in hypoxic stress in yeast, C. elegans, and mammalian cells (Jang et al, 2016;Jin et al, 2017;Miura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%